2018
DOI: 10.9775/kvfd.2018.20159
|View full text |Cite
|
Sign up to set email alerts
|

Tavuk, Bıldırcın ve Hibritlerinin Kromozom Karyotipleri ve Bantlanma Modeli Analizi

Abstract: To explore the incompatibility of hybrids between chickens and quails at the chromosome level, in the present study, chickens, quails, and their hybrids were selected and their chromosome karyotype and banding patterns were analyzed. The methods used comprised pre paring chromosomes from air-dried peripheral blood lymphocytes, the embryo method, G-banding, and C-banding techniques. The result revealed that the number of chromosomes (2n) of chicken, quail, and their hybrids was 78, with 10 pairs of macrochromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Besides, the results showed that EFNA5, FGFR3, NCAPG, FGF22, THBS2, genes related to sheep growth and development traits were enriched in PI3K-AKT, AMPK and other signaling pathways. Zhu et al [ 32 , 33 ] found that PI3K-AKT signaling pathway may be involved in poultry early embryonic development and early breast and leg muscle development. Further, we used the prolific Suffolk breeding group as a resource group to carry out GWAS research.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the results showed that EFNA5, FGFR3, NCAPG, FGF22, THBS2, genes related to sheep growth and development traits were enriched in PI3K-AKT, AMPK and other signaling pathways. Zhu et al [ 32 , 33 ] found that PI3K-AKT signaling pathway may be involved in poultry early embryonic development and early breast and leg muscle development. Further, we used the prolific Suffolk breeding group as a resource group to carry out GWAS research.…”
Section: Discussionmentioning
confidence: 99%